2018
DOI: 10.1002/aur.2039
|View full text |Cite
|
Sign up to set email alerts
|

Social difficulties in youth with autism with and without anxiety and ADHD symptoms

Abstract: Social difficulties inherent to autism spectrum disorder are often linked with co-occurring symptoms of anxiety and ADHD. The present study sought to examine the relation between such co-occurring symptoms and social challenges. Parents of adolescents with autism (N = 113) reported upon social challenges via the Social Responsiveness Scale (SRS) and anxiety and ADHD symptomatology via the Child Behavior Checklist (CBCL). Results revealed differences in SRS scores across co-occurring symptom subgroups (Anxiety,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 72 publications
2
21
1
1
Order By: Relevance
“…This study’s findings indicate that loneliness plays an important role in social anxiety and depression among autistic young adults. These results extend previous research that identified associations between autism features and mental health concerns among autistic people (Factor et al, 2017; Mayes et al, 2011; McVey et al, 2018) by identifying an indirect effect through loneliness. Similar effects have been identified in a non-clinical, neurotypical college student sample (Stice & Lavner, 2019), suggesting that parallel processes may be at play for autistic adults.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This study’s findings indicate that loneliness plays an important role in social anxiety and depression among autistic young adults. These results extend previous research that identified associations between autism features and mental health concerns among autistic people (Factor et al, 2017; Mayes et al, 2011; McVey et al, 2018) by identifying an indirect effect through loneliness. Similar effects have been identified in a non-clinical, neurotypical college student sample (Stice & Lavner, 2019), suggesting that parallel processes may be at play for autistic adults.…”
Section: Discussionsupporting
confidence: 88%
“…Researchers have identified positive links between autism features and mental health concerns. Scores on a measure of autism symptoms have been shown to be higher among autistic youth with symptoms of anxiety compared to those without (Factor et al, 2017; McVey et al, 2018). Given the core social component of autism (APA, 2013), social anxiety may be rooted in autism-specific risk factors including social confusion, withdrawal, and negative social interactions (Bellini, 2006; Spain et al, 2018; Wood & Gadow, 2010), and thus, ties between social anxiety and autism features have also been found among autistic adults (Bejerot et al, 2014).…”
mentioning
confidence: 99%
“…In our study, during school closedown period, children with ASD predominantly had changes in behavior, while most children in the control group maintained the previous behavior. Moreover, the causes for this behavior change reported by the parents were anxiety, irritability, obsession, hostility and impulsivity, all symptoms pre- viously described in the literature associated with this condition [16][17][18]. Emotion dysregulation is also a common issue experienced by individuals with ASD, and has been associated with maladaptive strategies [19].…”
Section: Discussionmentioning
confidence: 92%
“…We also know that school demands and social engagement [17,22,23] are stressors for children with ASD and taking this into account we could imagine that being at home, during quarantine, away from these challenges could comfort these children. However, during this period these children had to face a huge stressor for them: change of routines.…”
Section: Discussionmentioning
confidence: 99%
“…For caregiver report, however, the depression correlations were either no different or stronger than the SAS-A and SIAS associations, which provides little support for divergent validity; this pattern is likely confounded by differences in reporter, given that the SIAS is self-report. Furthermore, it is documented that the presence of anxiety is linked with greater reports of social difficulties for those with ASD (e.g., White & Roberson-Nay, 2009), and, in particular, SRS scores (Factor et al, 2017; McVey et al, 2018). While caregiver report on the SAS-A was positively correlated with the SRS, the association was not significantly different from the correlation between the SAS-A and the SIAS—given that SRS is parent report and SIAS is self-report, these findings are not unexpected.…”
Section: Discussionmentioning
confidence: 99%